Neighboring Rights: An Analytical and Comparative Study of Window Openings from The Perspectives of Afghan Civil Code and Hanafi Jurisprudence (Fiqh) - Fazli, Fazal Hadi; Maidin, Ainul Jaria; Omoola, Sodiq (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This research analytically and comparatively discusses the principles of window openings in residential buildings from the perspectives of Afghan Civil code and Hanafi jurisprudence (Fiqh). Every Muslim is obligated to respect the rights of their neighbors and ensure that the window openings does not lead to intrusions into their neighbors’ private lives. The Afghan Civil Code and Hanafi jurisprudence have specific regulations that require maintaining a minimum distance between windows and neighboring properties. The aim of this research is to clarify the principles of the Afghan Civil Code, Hanafi jurisprudence, and ethics concerning the protection of neighbors' rights and privacy, as well as to strengthen social order and prevent the potential harm and disputes. The significance of this research lies in presenting a balanced perspective between modern and traditional values in Afghan society, emphasizing that in window openings all Islamic, legal, and ethical principles and boundaries should be considered in the context of window placement. This research employs a doctrinal method along with descriptive, critical, and analytical approaches. It utilizes primary sources such as the Holy Quran, hadith, Afghan Civil Code, and other relevant national laws. Additionally, secondary sources including legal dictionaries, legal and jurisprudential books, articles, and relevant websites, have been thoroughly considered. All pertinent sources have been critically analyzed. This research provides specific guidelines regarding the principles of window openings and outlines how these can align with statutory and jurisprudential standards. Through its findings, the study aims to foster great respect for neighbors’ privacy and propose appropriate solutions for resolving legal disputes.